Mathematical Model for DetectingDiabetes in the Blood - Kwach, B.; Simwa, R.; Ongati, O. (My University, 2011)
This study presents a new mathematical model for Blood Glucose Regulatory System(BGRS) which includes epinephrine as a third variable in the form, ˙ Y = AY, and whose solution has been analyzed for equilibrium and stability to provide the blood glucose concentrations for diabetics and non-diabetics. We establish that the ﬁnal model is asymptotically stable compared to the existing models, that is, the eigenvalues of the coeﬃcient matrix are complex numbers with negative real parts. Furthermore, the resonance period for the ﬁnal model, that is, T0 = 2.9847134 hours, is far less than that of the existing model, showing that the glucose concentration returns to normal level within a shorter time.
Keywords: Mathematical model; Linear system; Resonance period